2003
DOI: 10.1016/s0022-5223(03)00396-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of postoperative systemic inflammatory reaction and pulmonary and renal complications after coronary artery surgery

Abstract: The interleukin 6 -174 G/C polymorphism modulates postoperative interleukin 6 levels and is associated with the degree of postoperative renal and pulmonary dysfunction and in-hospital stay after coronary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 16 publications
(26 reference statements)
1
41
0
1
Order By: Relevance
“…28 On the contrary, studies by Bittar et al 29 show that patients homozygous for the G allele had a significantly lower incidence of postoperative atrial fibrillation and a shorter hospital stay. These differences might occur due to the individual genetic predisposition for developing major or minor degrees of postoperative systemic inflammatory reaction.…”
Section: Discussionmentioning
confidence: 97%
“…28 On the contrary, studies by Bittar et al 29 show that patients homozygous for the G allele had a significantly lower incidence of postoperative atrial fibrillation and a shorter hospital stay. These differences might occur due to the individual genetic predisposition for developing major or minor degrees of postoperative systemic inflammatory reaction.…”
Section: Discussionmentioning
confidence: 97%
“…The IL-6 Ϫ174G/C polymorphism was investigated in three studies, of which only Guadino et al (14) found a significant association. This study found that in patients undergoing CABG, IL-6 Ϫ174GG, carriers had significantly higher elevations in perioperative creatinine versus non-GG carriers (P Ͻ 0.0001).…”
Section: ) Treszl Et Al Also Investigated This Polymorphism In Vlmentioning
confidence: 99%
“…This has been seen in other complex diseases, such as the discovery of a single nucleotide polymorphism (SNP) in complement factor H as a risk factor for macular degeneration (13). In AKI, genetic variation in inflammatory cytokines such as Tumor Necrosis Factor-alpha (TNF-␣) and Interleukin-6 (IL-6) have recently been proposed as risk factors (11,(14)(15)(16)(17). This is due to the role of inflammatory mediators in the pathophysiology of AKI, especially with ischemia and sepsis (1,18,19).…”
mentioning
confidence: 99%
“…Former research suggests that genetic diversity contributes to CSA-AKI. [5][6][7][8][9][10][11][12][13] Perioperative genetics have become an emerging field in recent years as clinicians could be enabled to strengthen existing clinical scores by also considering genetic risk factors predisposing to CSA-AKI.…”
Section: Introductionmentioning
confidence: 99%